2007
DOI: 10.1002/smll.200600539
|View full text |Cite
|
Sign up to set email alerts
|

Regular Dislocation Networks in Silicon as a Tool for Nanostructure Devices used in Optics, Biology, and Electronics

Abstract: Well-controlled fabrication of dislocation networks in Si using direct wafer bonding opens broad possibilities for nanotechnology applications. Concepts of dislocation-network-based light emitters, manipulators of biomolecules, gettering and insulating layers, and three-dimensional buried conductive channels are presented and discussed. A prototype of a Si-based light emitter working at a wavelength of about 1.5 microm with an efficiency potential estimated at 1% is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…[10][11][12] Recent studies have drawn a more detailed picture indicating that dislocations possess some exceptional electronic and optical properties induced by their small dimensions. [13][14][15] Possible applications of dislocations as active components of semiconductor devices have been discussed. 16 Note that the cross-section area of a dislocation core is about 1 nm 2 characterizing the defects itself as native nanowires embedded in a perfect matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Recent studies have drawn a more detailed picture indicating that dislocations possess some exceptional electronic and optical properties induced by their small dimensions. [13][14][15] Possible applications of dislocations as active components of semiconductor devices have been discussed. 16 Note that the cross-section area of a dislocation core is about 1 nm 2 characterizing the defects itself as native nanowires embedded in a perfect matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of a dislocation network in the interface of bonded wafers was impressively proved by a simple experiment [55]. Using electron beam induced current (EBIC) technique on a cross-section sample of a bonded wafer pair showed that carriers are transported predominantly along the interface.…”
Section: Electrical Measurements On Dislocationsmentioning
confidence: 98%
“…The evolution of the D-band luminescence has been also obtained on two-dimensional dislocation networks formed by wafer bonding. Photoluminescence, cathodoluminescence, and electroluminescence were applied for these studies (for instance [55,115,116]). All investigations proved a typical dependence of the resulting luminescence spectra on the type and distance of dislocations (or dislocation density) in the network.…”
Section: Optical Properties Of Dislocations-electron-hole Recombinatimentioning
confidence: 99%
“…Properties of dislocation networks formed by semiconductor wafer direct bonding were described in numerous publications (for reviews see, e.g. Kittler et al, 2007;Kittler & Reiche, 2009). The dislocation networks may be considered as model structures resulting in a lot of new information about the structure and properties of dislocations.…”
Section: Characterization Of Individual Dislocationsmentioning
confidence: 99%